Total cost of care increases significantly from early to mild Alzheimer's disease: 5-year ALSOVA follow-up. (10th July 2021) - Jetsonen, Viivi; Kuvaja-Köllner, Virpi; Välimäki, Tarja; Selander, Tuomas; Martikainen, Janne; Koivisto, Anne M
Abstract: Introduction: We studied the costs of formal and informal care in relation to Alzheimer's disease (AD) progression. Methods: 231 persons with AD with a family caregiver were followed up for 5 years. The Clinical Dementia Rating Scale—Sum of Boxes (CDR-SB) was used to measure AD progression. Health and social care unit costs were used for formal care costs. An opportunity cost method for lost leisure time was applied to analyse the cost of informal care. Results: Total cost of care in early stage AD (CDR-SB ≤ 4) was 16, 448€ (95% CI 13, 722–19, 716) annually. In mild (CDR-SB 4.5–9), moderate (CDR-SB 9.5–15.5) and severe (CDR-SB ≥ 16) AD, the total costs were 2.3, 3.4 and 4.4 times higher, respectively. A one-unit increase in CDR-SB increased the total, formal and informal costs by 15, 11 and 18%, respectively. Conclusions: Compared to early AD, the costs of total, formal and informal care are remarkably higher already in mild AD. This finding emphasises early diagnosis, interventions and family support for persons with AD and their caregivers.